Study of knowledge, attitude, and practice regarding birth spacing and methods available for spacing in rural Haryana, India - Yadav, Bindoo; Pandey, Santvana (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: Birth spacing is defined as the time interval between two births. India has average birth spacing of 22 months, i.e. little less than two years, despite wide knowledge of contraception. Objective of present study was to investigate the knowledge, attitude, and practice regarding birth spacing and methods available for spacing in rural Haryana amongst sexually active married females of reproductive age. Methods: Cross sectional study of 500 sexually active, married females of reproductive age with at least one live issue and not meeting any exclusion criteria was carried at SGT medical college, Gurgaon during 3 months from August 2017. Results: Awareness of need for birth spacing was very high (82.6%) in females interviewed, with 70% of females being aware of birth spacing benefits as well as keen to opt for birth spacing but even higher count of females (92.6%) reporting requiring husband’s consent for birth spacing. Only 40% females were practising birth spacing with 14.6% of females reporting in-law’s opposition as reason for not practising birth spacing. Conclusions: Education is a major factor improving awareness of need as well as benefits of child spacing, with all college studied females being aware of both. Education also leads to improvement in keenness for practising child spacing as well as having lesser opposition to practise of child birthing. Females with only girl child/children were less keen to practise child spacing. Rural geographies still have health personnel as significant source imparting awareness of child spacing.